2009
DOI: 10.1017/s0020859009000017
|View full text |Cite
|
Sign up to set email alerts
|

Cash Crops and Freedom: Export Agriculture and the Decline of Slavery in Colonial West Africa

Abstract: SummaryThis article argues that the greatest economic and social transformations of the early colonial period in West Africa, the “cash-crop revolution”, and “the slow death of slavery” and debt bondage, had stronger and more varied causal connections than previously realized. The economic circumstances of late nineteenth and early twentieth-century West Africa delayed and diluted abolitionist measures. Indeed, the coercion of labour, through the exercise of property rights in people, contributed to the speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Perhaps partly because they paid little attention to institutional matters, such as the organization of labour, but also because they shared in a collective amnesia, in the early years after Independence, about the fact that slavery had ever existed within African societies; Austin, ‘Cash crops and freedom’, pp. 8–9.…”
mentioning
confidence: 99%
“…Perhaps partly because they paid little attention to institutional matters, such as the organization of labour, but also because they shared in a collective amnesia, in the early years after Independence, about the fact that slavery had ever existed within African societies; Austin, ‘Cash crops and freedom’, pp. 8–9.…”
mentioning
confidence: 99%
“…The export economy drove the expansion of irrigation and changes to production systems during the colonial period ( Figure 2). Enforced by colonial administrations, export production continued to increase despite declining terms of trade (Austin, 2009). The domestic economy and markets declined due to expatriation of the revenue from the export economy; closure of manufacturing industries; discouragement of interregional trade; disruption of local food production and livelihoods (Worboys, 1988); and payment in provisions rather than cash for domestic and farm labour on plantations and settler estates.…”
Section: Drivers Of Irrigation Expansion and Production Changesmentioning
confidence: 99%
“…Gareth Austin has shown that the transition from slavery to freedom was facilitated by the development of cash crops (2009). Those who owned profitable land grew crops that earned them relatively high profits.…”
Section: The Primacy Of Productionmentioning
confidence: 99%